A Double Standard: The Respective Responsibilities of English and French-language Canada in the German Refugee Crisis - Anctil, Pierre (Canadian Jewish Studies / Études juives canadiennes, 2019)
In their seminal work dealing with the refugee crisis of the late thirties and early forties, Abella and Troper describe the inner workings of the Canadi- an Federal bureaucracy with regard to admitting Jews from Nazi-occupied Europe. Their study, supported by solid archival work, demonstrates the com- plex and, at the time, hostile reception that Canadian politicians gave to Jews knocking on their door. The authors’ narrative is much weaker, however, when they address the question of French Canada. In this article, I seek to demon- strate that Abella and Troper’s conclusions regarding Francophones are not based on any conclusive documentation. Using recent historical research and French-language sources, a remarkably different portrait emerges of the way Quebec understood the question of Jewish refugees and reacted to their plight.